Expression profiling of immune genes in classical swine fever vaccinated indigenous and crossbred piglets - PATHAK, SHALU KUMARI; SAH, VAISHALI; SAILO, LALRENGPUII; CHAUDHARY, RAJNI; SINGH, AKANSHA; KUMAR, RAVI; KUMAR, AMIT (The Indian Journal of Animal Sciences, 2017)
Classical swine fever is a highly contagious disease of pigs which courses from life-threatening to asymptomatic, depending on the virulence of the virus strain and the immune-competence of the host. The present study was undertaken to investigate the expression of immunologically important genes, viz. IFNα, IFNβ, SLA, SLA-2, SLA-DR, Ii, SLA-DM, CSK and JUN and to ascertain genetic group differences on the basis of humoral immune response. Blood samples were collected from 5 indigenous and 6 crossbred piglets at pre-vaccination and after 28th day of classical swine fever (CSF) vaccination. On 28th day, the competitive Enzyme Linked Immunosorbent Assay (cELISA) revealed poor humoral immune response (E2 antibodies) in indigenous piglets (84.80%) as compared to crossbred piglets (98.33%) in response to CSF vaccination. The expression level of genes was analyzed in three ways, viz. indigenous 28th day post-vaccination (28dpv) versus pre-vaccination, crossbred 28th day post-vaccination versus pre-vaccination and crossbred 28th day post-vaccination versus indigenous 28th day post-vaccination. The study showed that IFNα, IFNβ, SLA, SLA-2, Ii, SLA-DM, CSK and JUN were significantly upregulated in crossbred piglets than indigenous piglets at 28th day post-vaccination. But the SLA-DR was significantly downregulated in CSF vaccinated crossbred over indigenous piglets.